Pengaruh Positive Psychological Capital dan Growth Mindset Terhadap Individual Wellbeing dan Educational Consumption Expenditure Patterns Keluarga Petani di Kepulauan Selayar - Dilla Febriana; Thamrin Tahir; Muhammad Hasan; Muh Ihsan Said Ahmad; Andi Annisa Sulolipu (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to examine the influence of positive psychological capital and growth mindset on individual well-being and educational consumption expenditure patterns in farming households in Selayar Islands Regency, both through direct and indirect influences. This study used a quantitative approach with a causal-associative design. The study population included farmers in Bontomanai, Benteng, and Buki Districts, with the sample determined through purposive sampling technique based on the criteria of farming households with school-age children. Data collection was conducted using a five-point Likert-scale questionnaire, while data analysis was conducted using the Structural Equation Modeling (SEM) method. The results showed that positive psychological capital and growth mindset had a positive and significant effect on individual well-being and household educational consumption expenditure patterns. In addition, individual well-being was proven to have a significant effect on educational consumption expenditure patterns and acted as a mediating variable in the relationship between positive psychological capital and growth mindset and educational consumption expenditure patterns. These findings confirm that strengthening the psychological aspects of farming families plays a crucial role in improving individual well-being and supporting the sustainability of educational investment amidst economic constraints.